Feasibility of using ultrasound to measure preterm body composition and to assess macronutrient influences on tissue accretion rates - McLeod, G.; Geddes, D.; Nathan, E.; Sherriff, Jillian; Simmer, K.; Hartmann, P. (Elsevier Ireland Ltd, 2013)
Background and aims: To assess ultrasound as a method for (i) measuring body composition (BC) of preterm infants and for (ii) assessing the influence of macronutrient intakes on tissue accretion rates. Methods: Preterm ultrasound studies of four anatomical sites were performed approximately every three weeks from birth to corrected-term age. Preterm measurements were compared to foetal reference data. Duplicate scans at each site were taken on a subset of infants to test the reproducibility of the method, assessed as the coefficient of variation (CV). The influence of measured macronutrient intakes on preterm BC was assessed by regression analysis. Results: Median (range) gestation and birth weight of 40 preterm infants were 27 (23–29) weeks and 1022 (480–1475) g, respectively. Accretion rates of adipose and muscle tissues were not uniform across the four sites. Relative to the foetus, preterm adipose tissue thickness was reduced at an equivalent (corrected) gestation, but towards term, a faster accretion rate of subcutaneous abdominal adipose and limb muscle tissue was evident. Timing of fortification (p = 0.012), enteral carbohydrate intake (p = 0.008) and the protein energy ratio of intakes (p = 0.038) moderated the ratio of adipose to muscle tissue accretion over the four sites by − 0.004, − 0.048 and − 0.042, respectively. Conclusions: Ultrasound provides a non-invasive, portable method of assessing changes in subcutaneous adipose tissue and muscle accretion and appears sufficiently sensitive to detect influences of macronutrient intakes on accretion rates from birth. The method warrants further investigation as a bedside tool for measuring BC of preterm infants.